ダイ15ジ ナンキョク チイキ カンソクタイ ナツタイ ガイホウ 1973-1974 - 村山, 雅美; ムラヤマ, マサヨシ; MURAYAMA, Masayoshi (国立極地研究所, 1974)
P(論文) The Japanese Antarctic activities have been resumed on the occasion of Japan's participation in the International Geophysical Year, 1957-1958. The 1st Japanese Antarctic Research Expedition (JARE), under Dr. T. NAGATA'S leadership, was organized to establish a scientific station in Antarctica, and was dispatched on board the icestrengthened ship SOYA. In 1957 Syowa Station was established at 69°00'S,39°35/E on Ongul Island, off Soya Coast, Prince Haraid Land. Syowa was temporarily closed between 1962 and 1965, because of the superannuation of the SOYA. During the cessation period, the icebreaker FUJI was built. Operated by the Japan Maritime Self Defence Force, the FUJI was placed in commission and the 7th JARE reactivated Syowa in 1966. Since then, the facilities at the station have been rapidly amplified year by year. The present report outlines scientific and logistic activities of the summer party of the 15th JARE in the Southern Ocean and in the vicinity of Syowa during the period between the departure from Fremantle, Australia on December 16, 1973 and the arrival at Cape Town, South Africa on March 9, 1974, The 15th JARE consisting of 40 men was led by the author. Thirty of the 40 scientists and technicians constituted the wintering party led by Mr. Nozomi MURAKOSHI, deputy leader of the Expedition. The scientific program of the 15th JARE was prepared by the Planning Committee (Chairman, Dr. T. NAGATA) of Polar Research Center, National Science Museum, which was reorganized into the National Institute of Polar Research in September 1973. The program is a part of the long-term yearly plan listed in Table 4, and has been officially approved by the Promoting Headquarters of JARE presided by the Minister of Education. It must be noted here that the environmental science, in connection with biology, human physiology and geochemistry, will be studied at a newly established environmental science laboratory (shown in Fig. 1). Also, the inland survey is to be counted for much by a team of glaciologists, ...